(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg YfO GfJaGA TQWg, GdeQGO Hg TQW GdGeQ ShGA cGf (B.. (3hHGdPGJ Ch HhGSWI chfg TQW ddeCehQ Hg aEf TQhWg JQLY dTQhW GdCeQ HeYfi HeYfi hPdc dCfg dhdGgG deG MUdJ GdbOQIs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg EfgeG Cj GdELeGd Gdhaj hGdHjGf Gdhaj, bhdg dYOe ehaJg HGdhVY (B.. (3de jcf XGgQ efg, bhdg dOjg(B: (3Cj dOi Pdc GdCMO(B. (3GfJgi GdebUhO dfG ef TQM GdLRA GdChd ef GdcaGjI(B.s
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs